Community policing goes south: policy mobilities and new geographies of criminological theory - Beck, Max Méndez (The British journal of criminology, 2019)
Policymakers seeking to design more effective crime control strategies increasingly reference ‘best practices’ developed in other contexts, enabling the translocal mobility of ‘zero tolerance’ or ‘hotspot policing’. Recent work on policy mobilities shows that such policies, and the conceptual models underlying them, are often contested and modified as they travel. Connecting emergent scholarship on crime control policy mobilities to recent calls to extend criminological theorization outside the global North, this article seeks to understand what happens when community policing travels. Specifically, it unpacks the often-implicit models of urban governance underlying community policing, examining the mobilities and mutations of these conceptual models as community policing is exported from cities in the United States to inner-city neighbourhoods in Kingston, Jamaica.